Corpus Callosum Remodeling in Glioma: Constancy of Fiber Density and Anisotropy in MRI. (13th March 2022) - Pareek, Vikas; Paul, Subhadip; Roy, Prasun K.
ABSTRACT: Corpus callosum (CC) is the primary fiber system bridging the cerebral hemispheres and is of critical importance for glioma migration which downgrades the prognosis. Here we present the specific pattern of CC restructuring in glioma patients. We probe that the magnetic resonance imaging-based fiber count decrease can be a ready noninvasive indicator of glioma aggressivity and prognosis. We find that to maintain the callosal neural transmission efficiency, the optimum architectural density of white matter fibers remains unchanged, even though there is gross fiber loss. This adaptation occurs by CC's isotonic restructuration, a protective compensatory behavior for maintaining CC's optimal functional efficiency despite malignant infiltration.